1986
DOI: 10.1002/ajmg.1320240104
|View full text |Cite
|
Sign up to set email alerts
|

Diploid‐triploid mosaicism: Report of necropsy findings

Abstract: This is the first report of necropsy findings associated with diploid-triploid mosaicism. The important pathological findings are presented and compared to those of pure triploidy and those noted in noninvasive studies of diploid-triploid mosaics. The clinical findings in this patient are compared with those of other reported cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…Peripheral blood karyotyping indicated triploidy described as 69, XXX in a total of 100 examined metaphases (Figure 2). Chromosome studies on cultured skin biopsy revealed mosaicism for triploid cell line described as 69, XXX[42]/46,XX [8], 84% cells were triploid and 16% were normal female karyotype. The aim of the FISH study was to determine the mosaic level in peripheral blood and skin.…”
Section: Resultsmentioning
confidence: 99%
“…Peripheral blood karyotyping indicated triploidy described as 69, XXX in a total of 100 examined metaphases (Figure 2). Chromosome studies on cultured skin biopsy revealed mosaicism for triploid cell line described as 69, XXX[42]/46,XX [8], 84% cells were triploid and 16% were normal female karyotype. The aim of the FISH study was to determine the mosaic level in peripheral blood and skin.…”
Section: Resultsmentioning
confidence: 99%
“…Allerdings treten die typischen Symptomkombinationen und Fehlbildungen variabel auf, was die Blickdiagnose erschweren kann [6,23,24]. Auch zeigen Kinder mit Mosaiken, bei denen triploide mit diploiden Zelllinien gemeinsam vorhanden sind, die typischen klinischen Symptome nur in abgemilderter Form [25,26]. Diese Kinder kön-nen Berichten nach über das Säuglingsalter hinaus überleben [27].…”
Section: Diskussionunclassified
“…Diploid–triploid mosaicism is rare (only 20–25 liveborn have been reported) (1–22) but patients with diploid–triploid mixoploidy may survive beyond the neonatal period owing to less severe developmental anomalies than in pure triploidy. As major psychomotor retardation is usually observed in 2n/3n mosaicism, it is important to recognize this chromosomal abnormality before birth.…”
Section: Diploid–triploid Mosaicismmentioning
confidence: 99%